2005
DOI: 10.2337/diabetes.54.5.1371
|View full text |Cite
|
Sign up to set email alerts
|

Differential Association of Basal and Postprandial Plasma Ghrelin With Leptin, Insulin, and Type 2 Diabetes

Abstract: To gain further insight into the regulatory role of insulin and leptin on plasma ghrelin, 56 normal weight, 128 normoinsulinemic obese, 121 hyperinsulinemic obese, and 30 type 2 diabetic normoinsulinemic and 75 type 2 diabetic hyperinsulinemic obese patients were examined. In the obese subjects, basal hyperinsulinemia was associated with significantly lower ghrelin independent of BMI, age, and leptin. In normoinsulinemic (normal weight and normoinsulinemic obese) subjects, ghrelin was inversely related to step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
85
2
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 57 publications
(73 reference statements)
18
85
2
6
Order By: Relevance
“…Similarly, both leptin and ghrelin concentrations change markedly following feeding, with ghrelin decreasing [32] and leptin increasing [33], and both respond to exercise [34,35]. These hormones both play a role in the regulation of bone metabolism [36,37], and, in the case of leptin, might also be involved in a pathway linking bone metabolism and energy metabolism homeostasis [38].…”
Section: 4mentioning
confidence: 99%
“…Similarly, both leptin and ghrelin concentrations change markedly following feeding, with ghrelin decreasing [32] and leptin increasing [33], and both respond to exercise [34,35]. These hormones both play a role in the regulation of bone metabolism [36,37], and, in the case of leptin, might also be involved in a pathway linking bone metabolism and energy metabolism homeostasis [38].…”
Section: 4mentioning
confidence: 99%
“…Given the high prevalence of diabetes mellitus globally as well as the associated macro-and microvascular complications, identifying the factors that may affect its progress and cause the pathological changes in the body is important (Ceriello, 2006;Edmann et al, 2005). The secretion of ghrelin, an appetite-stimulating hormone in humans produced primarily in the gastrointestinal tract has been found to play a role in the progression of diabetes (Buss et al, 2014;Klok et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Low fasting ghrelin concentrations have been consistently associated with obesity independent of the presence of type 2 DM in people and negative feedback from excess leptin produced by the numerous adipocytes has been implicated in this process 38, 39, 40, 41, 42. In contrast, a previous study in obese and lean cats found that fasting serum acylated ghrelin concentrations were in fact slightly higher in an obese state (though the mean difference was only 9 pg/mL) 43.…”
Section: Discussionmentioning
confidence: 93%